Impact and Challenges of Cloud based E-Learning in the Indian Education Sector - Venkatraman, B.; Seethalekshmy, N. (Indian Journal of Computer Science, 2017)
Web based learning has taken a new turn over the years. With the proliferation of Cloud computing and similar paradigms like Mobile Cloud Computing, e-learning technology has created waves in the education sector. However, in India this has been low due to lack of infrastructure and incorrect allocation of esources. Over a period of time it has been observed that although a bounty of cloud resources are available, to a large extent accessing these resources has become a major challenge. To this end, in this manuscript we look at some of the foremost challenges of a cloud based service and its direct impact on the growth of E-learning in the Indian Education Sector.